Penguatan Daya Saing Umkm Desa Melalui Digitalisasi Pemasaran Dan Manajemen Di Desa Amoito, Kecamatan Ranomeeto Barat, Kabupaten Konawe Selatan - La Ode Anto; La Ode Suriadi; Erwin Hadisantoso; Nursaban Rommy Suleman; Riski Amalia Madi; Nurul Ittaqullah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service activity focuses on Strengthening the Competitiveness of Village MSMEs (Micro, Small, and Medium Enterprises) through Digital Marketing and Management in Amoito Village, West Ranomeeto District, South Konawe Regency. The program aims to increase the turnover and operational efficiency of MSMEs, while instilling a culture of transparent and accountable financial management through the adoption of digital technology. This activity utilizes a descriptive qualitative and participatory action method, which includes needs assessment, intensive socialization, implementation assistance, and post-training monitoring. The results indicate that the digital intervention successfully expanded the MSMEs' market reach through e-commerce and social media, strengthened the accountability of financial management, and increased time efficiency in business operations. Nevertheless, challenges still exist regarding the consistency of MSME actors in recording daily transactions and the need for adequate hardware support.